Solvent‐Free Aerobic Oxidation of Ethylbenzene Promoted by NHPI/Co(II) Catalytic System: The Key Role of Ionic Liquids. Issue 1 (5th November 2019) - Dobras, Gabriela; Sitko, Magdalena; Petroselli, Manuel; Caruso, Manfredi; Cametti, Massimo; Punta, Carlo; Orlińska, Beata
Abstract: The synergistic action between imidazolium based ionic liquid (IL) [bmim][OcOSO3 ] and Co(II)/ N ‐hydroxyphthalimide (NHPI) systems in the catalytic aerobic oxidation of ethylbenzene under solvent‐free conditions have been here demonstrated by reaching a 35 % conversion with 83 % of selectivity in acetophenone at 80 °C. This highly performing catalytic system have been selected after screening several different IL and Co(II) salt combinations, and making sure that the complete solubilization of the polar NHPI in the lipophilic medium, without thus requiring any chemical modification of the organic catalyst, could be attained. This solubilizing effect can be ascribed to a direct interaction between [bmim][OcOSO3 ] IL and NHPI as revealed by a detailed NMR investigation which also allowed to exclude the formation of higher IL aggregates in the form of micelles or vesicles. Abstract : Selective Oxidation : The positive effect of the addition of catalytic amounts of [bmim][OcOSO3 ] in NHPI/Co(II) catalyzed oxidation of ethylbenzene which is not ascribable to polar effect have been reported. The IL promoted the direct solubilization of NHPI in hydrocarbon by means of interaction with small ion‐pairs aggregates of IL.